Platysognathus gen. nov. a new genus of railroad-worm beetle (Coleoptera: Phengodidae, Mastinocerinae) from Colombian Amazonía - Uchima-Taborda, Diego; Hortúa, Andrés Lugo De La; Vega-Badillo, Viridiana; Fernández, Fernando; Zaragoza-Caballero, Santiago (Zootaxa, 2025)
A new genus, Platysognathus gen. nov., and its type species Platysognathus amazonicus sp. nov. are described with specimens collected in the Colombian Amazon. This genus presents two characteristics documented for the first time in the family: the presence of an irregularly rhomboid mandibular tooth and a serrated genital flagellum. These characteristics together with the presence of a slightly asymmetrical genitalia and tarsal combs in the first pro- and mesotarsomere separates Platysognathus from other genera of Phengodidae with 11 antennomeres. This is the first genus of Phengodidae described with material from the National Natural Parks “Yaigojé Apaporis” and “Serranía del Chibiriquete”, the latter being a natural and cultural heritage of humanity. This study, in addition to updating the state of knowledge of the group for the country, highlights the importance of natural parks as reservoirs of Phengodidae and insect diversity.